Fertilizers organic coffee, with use chicken manure in replacing yhe mineral fertilizer - Fernandes, André Luís Teixeira; Santinato, Felipe; Ferreira, Rodrigo Ticle; Santinato, Roberto (Coffee Science - ISSN 1984-3909, 2014)
The aim of this work was to study the technical feasibility in reducing levels of the nutrients nitrogen (N), phosphorus (P), potassium (K) and sulfur (S), mineral fertilizer used in coffee, Red Catuai cultivar IAC-144 by organic fertilization with chicken manure in increasing doses of 2.5, 5.0, 10.0 and 20.0 t ha-1 increased proportionally to the dose of mineral fertilizer from the planting to the third coffee production. In the three harvests, all treatments were significantly superior in production compared to the control, 107-145%, indicating the importance of N, P, K and S in coffee cultivation in the “cerrado”, vegetation of the Brazilian interior. Among the treatments, the highest dose of manure (20.0 t ha-1) was significantly more productive treatment, and the remaining doses were not significantly different, although they have provided increases 9-19% in productivity, compared to treatment only mineral. On the ground, it was observed that, depending on the dose of organic fertilizer, there was an increased cation exchange capacity (CEC), the levels of calcium (Ca), phosphorus (P), boron (B), potassium (K) , zinc (Zn) and manganese (Mn), and lower levels of copper (Cu). The use of higher doses of mineral fertilizer, there was reduction in pH, base saturation (V%), and Ca and Mg. In larger doses of manure, no significant chemical changes to the pH and V%. Organic matter practically remained stable. The contents of N, P, K and S leaf in all treatments were adequate and deficient in witness. At the doses used of N, P, K and S of the experiment, one can recommend a reduction from 14 to 100% of C, 50 to 100% of P, from 8 to 58% K and 21 to 100% of S.